Pengaruh Daya Tarik Wisata, Harga Tiket, Dan Aksesibilitas Terhadap Kepuasan Wisatawan Di Wisata Alam Setigi Gresik - Ahmad Rizqi Al Aisar; N. Rachma; Rahmawati Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research is to find out and analyze tourist attractions, ticket prices and accessibility to tourist satisfaction in Gresik setigi nature tourism. The population in the study was natural tourist attractions setigi Gresik. The sampling technique uses purposive sampling which is a sample collection technique based on certain criteria with 100 respondents. The analysis technique uses multiple linear regression analysis. The results showed that the variables of tourist attractions (X1), ticket prices (X2) and accessibility (X3) had a contribution to the tourist satisfaction variable (Y) of 70.7% and the remaining 29.3% was explained by other independent variables that were not in the study. And simultaneously and partially tourist attraction, ticket price and accessibility have a significant effect on tourist satisfaction.  Keywords: Tourist Attraction, Ticket Price, Accessibility, Tourist Satisfaction